Costly information acquisition, social networks, and asset prices : experimental evidence - Halim, Edward (2020)
We design an experiment to study the implications of information networks for incentives to acquire costly information, market liquidity, investors' earnings, and asset price characteristics in a financial market. Social communication crowds out information production as a result of an agent's temptation to free ride on the signals purchased by her neighbors. Although information exchange among traders increases trading volume, improves liquidity, and enhances the ability of asset prices to reflect the available information in the market, it fails to improve price informativeness. Net earnings and social welfare are higher with information sharing due to reduced acquisition of costly signals.